Neutrophils in pancreatic cancer: Potential therapeutic targets - Jiang, Wenkai; Li, Xin; Xiang, Caifei; Zhou, Wence (Frontiers in Oncology, 2022)
Pancreatic cancer is a digestive system malignancy and poses a high mortality worldwide. Traditionally, neutrophils have been thought to play a role in acute inflammation. In contrast, their importance during tumor diseases has been less well studied. Generally, neutrophils are recruited into the tumor microenvironment and exert inflammation and tumor-promoting effects. As an essential part of the tumor microenvironment, neutrophils play diverse roles in pancreatic cancer, such as angiogenesis, progression, metastasis and immunosuppression. Additionally, neutrophils can be a new potential therapeutic target in cancer. Inhibitors of cytokines, chemokines and neutrophil extracellular traps can exert antitumor effects. In this review, we describe the role of neutrophils in the development and progression of pancreatic cancer, discuss their potential as therapeutic targets, and aim to provide ideas for improving the prognosis of patients with this malignant tumor disease.